Structured Water Play and Courage Development in Children with ADHD During Swimming Instruction - Nukeu Vianka; Muhammad Nur Alif; Rizal Ahmad Fauzi (Journal Coaching Education Sports, 2026)
This study aimed to examine the effect of structured water play on improving courage in children with ADHD during swimming instruction. The study employed a Single Subject Research (SSR) design with an A1–B–A2 withdrawal model. The participant was a six-year-old boy diagnosed with ADHD, selected using a case study approach. The intervention was conducted over 12 sessions consisting of baseline (A1), intervention (B), and follow-up (A2) phases. Data were collected through systematic observation of courage-related behaviors and pre-test and post-test questionnaires measuring aquatic fear levels. The instruments included an observation sheet adapted from SNAP-IV, Conners, and ADHD RS-5, as well as a fear-level questionnaire. Data were analyzed using SSR visual analysis techniques, including trend direction, level changes, stability, and Percentage of Non-Overlapping Data (PND). The findings demonstrated a consistent increase in courage during the intervention phase, which was maintained during the follow-up phase. In the shallow pool condition, the PND value reached 66%, indicating a moderate effect, while in the deep pool condition the PND value reached 100%, indicating a strong effect. Questionnaire results also showed a reduction in aquatic fear. These findings indicate that structured water play is an effective adaptive pedagogical strategy for enhancing courage and emotional readiness in children with ADHD during swimming instruction and supports the implementation of inclusive physical education practices.